Ответ:
y= - +6,5
Пошаговое объяснение:
y'=-x
y=-+C
y(3)=2 подставляем:
2=- *+С
С= 2+4,5=6,5
Получаем частное решение: y= - +6,5
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
y= -![\frac{1}{2} \frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
+6,5
Пошаговое объяснение:
y'=-x
y=-![\frac{1}{2} \frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
+C
y(3)=2 подставляем:
2=-
*
+С
С= 2+4,5=6,5
Получаем частное решение: y= -![\frac{1}{2} \frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
+6,5